2009
DOI: 10.1007/s15010-008-7474-8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Surgical Site Infection Guidelines in Italian Cardiac Surgery Units

Abstract: Adherence to CDC SSI guidelines in Italy is fair. The evidence of the recommendation does not influence adherence. Organizational improvements, especially those regarding hair removal and the timing of antibiotic prophylaxis, should be implemented in most hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Inappropriate SAP prescribing has consistently been reported in both Australian 26,27,28,29 and international 30,31,32,33,34,35,36,37,38,39,40,41 literature with a broad range; Ou et al 40 reported a 9.4% overall rate of appropriateness, while Hohmann et al 39 reported an overall compliance rate of 70.7%. The Surgical NAPS data demonstrated SAP appropriateness rates of 53.6% for procedural prescriptions and 36.9% for postprocedural prescriptions, with 48.7% as the combined overall rate of appropriateness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate SAP prescribing has consistently been reported in both Australian 26,27,28,29 and international 30,31,32,33,34,35,36,37,38,39,40,41 literature with a broad range; Ou et al 40 reported a 9.4% overall rate of appropriateness, while Hohmann et al 39 reported an overall compliance rate of 70.7%. The Surgical NAPS data demonstrated SAP appropriateness rates of 53.6% for procedural prescriptions and 36.9% for postprocedural prescriptions, with 48.7% as the combined overall rate of appropriateness.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate SAP prescribing has consistently been reported in both Australian [26][27][28][29] and international [30][31][32][33][34][35][36][37][38][39][40][41] literature with a broad range; Ou et al 40 Abbreviation: ND, no data.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgeons and nurses continue to regard hair as a risk factor for infection, and hair removal is still frequently performed before surgery (Pan et al . , Henrik et al . ).…”
Section: Discussionmentioning
confidence: 94%
“…Ancak CAE'larının önlenmesine yönelik yayınlanan güncel kılavuzlar ameliyat bölgesindeki tüylerin gerekli olmadıkça temizlenmesi önerilmemektedir (1,5,(14)(15)(16)(17). Konu ile ilgili yapılan çalışmalarda tüylerin enfeksiyon için bir risk faktörü olarak görüldüğü ve dünya genelinde ameliyattan önce genellikle temizlendikleri belirtilmektedir (18)(19)(20). Bu çalışmada da hastaların çoğunluğunun ameliyat bölgesindeki tüylerinin gerekli olup olmadığı düşünülmeksizin rutin olarak temizlendiği belirlenmiştir.…”
Section: Ameliyat öNcesi Duş/banyounclassified